Tumour resistance in induced pluripotent stem cells derived from naked mole-rats - Shingo Miyawaki; Yoshimi Kawamura; Yuki Oiwa; Atsushi Shimizu; Tsuyoshi Hachiya; Hidemasa Bono; Ikuko Koya; Yohei Okada; Tokuhiro Kimura; Yoshihiro Tsuchiya; Sadafumi Suzuki; Nobuyuki Onishi; et al. (Nature Communications, 2016)
The naked mole-rat exhibits an exceptional resistance to cancer. Here, the authors show that induced pluripotent stem cells derived from the naked mole-rat lack teratoma-forming tumorigenicity due to a naked mole-rat-specific ARF-dependent tumour-suppression mechanism.